1999
DOI: 10.1104/pp.119.4.1437
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Sec21p and Sec23p Homologs. Probable Coat Proteins of Plant COP-Coated Vesicles1

Abstract: Intracellular protein transport between the endoplasmic reticulum (ER) and the Golgi apparatus and within the Golgi apparatus is facilitated by COP (coat protein)-coated vesicles. Their existence in plant cellshas not yet been demonstrated, although the GTPbinding proteins required for coat formation have been identified. We have generated antisera against glutathione-S-transferase-fusion proteins prepared with cDNAs encoding the Arabidopsis Sec21p and Sec23p homologs (AtSec21p and AtSec23p, respectively). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
96
0
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 51 publications
2
96
0
8
Order By: Relevance
“…A similar distribution has been reported for Sar1p in yeast . Interestingly, overexpression of Sar1p in Arabidopsis alters this relationship, such that considerably more AtSar1p is present in the cytosol than on the membranes (Bar-Peled and Raikhel, 1997).Although we had previously obtained weak cross-reactions with AtSec23p antibodies against polypeptides present in membrane or cytosolic fractions prepared from yeast and (Movafeghi et al, 1999), none of the plant COPI or GTPase antisera reacted in this way ( Figure 1A). This suggests that the major antigenic determinants are localized to nonhomologous domains of COP-vesicle coat proteins.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…A similar distribution has been reported for Sar1p in yeast . Interestingly, overexpression of Sar1p in Arabidopsis alters this relationship, such that considerably more AtSar1p is present in the cytosol than on the membranes (Bar-Peled and Raikhel, 1997).Although we had previously obtained weak cross-reactions with AtSec23p antibodies against polypeptides present in membrane or cytosolic fractions prepared from yeast and (Movafeghi et al, 1999), none of the plant COPI or GTPase antisera reacted in this way ( Figure 1A). This suggests that the major antigenic determinants are localized to nonhomologous domains of COP-vesicle coat proteins.…”
mentioning
confidence: 81%
“…After centrifugation at 100,000g for 3 hr in a swinging bucket rotor, the membranes collecting at the 30/35% interphase were removed, diluted with an equal volume of medium C, and recentrifuged at 70,000g for 20 min. (Previous measurements of marker enzymes and proteins had indicated that cauliflower Golgi membranes equilibrated at sucrose densities between 30 and 35% [Movafeghi et al, 1999].) Membrane pellets were resuspended in 2 to 4 mL of 300 mM KI (dissolved in medium C containing 200 mM sucrose) and rotated for 45 min at 4ЊC before being recentrifuged at 70,000g for 20 min.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the identification of Sec12p and Sar1p in plants and their functional complementation in yeast (d'Enfert et al, 1992) suggests that these components control this pathway. Second, the identification of COPII coat components in plants (Movafeghi et al, 1999) and the identification of COPI vesicles in plants suggest that the principle of non-clathrin-coated vesicle formation has been well documented . Whether COPII transport occurs in a vesicular or a tubular manner is not relevant at this stage, and we do not wish to endorse either model; however, because the term COPII vesicles is used in the yeast and mammalian literature, it seems appropriate to use this term for plants as well until hard evidence against this has been presented.…”
Section: Sec12p Overexpression Inhibits Copii Transport Through the Dmentioning
confidence: 99%
“…However, proteins with analogous functions have not yet been identified in plants. Plant homologs of components of the COPI and COPII vesicle coats have been identified and some characterization studies have been carried out (d'Enfert et al, 1992;Regad et al, 1993;Bar-Peled and Raikhel, 1997;Takeuchi et al, 1998;Movafeghi et al, 1999;Contreras et al, 2000;Pimpl et al, 2000;Vernoud et al, 2003;daSilva et al, 2004;Yang et al, 2005;Stefano et al, 2006). Although this area of research is currently one of great interest and activity, knowledge of transport in the early secretory pathway of plants still lags behind that from yeast and mammalian systems.…”
mentioning
confidence: 99%